Eco-exergia como indicador de condição ambiental em bacias hidrográficas na savana neotropical - Marden Seabra Linares (2017)
Lotic ecosystems are among the most threatened ones by human activities on a global scale. To protect and conserve the environmental quality of these ecosystems, accurate measurements of how they respond to natural and anthropogenic changes are necessary, making the use of ecological indicators essential. Among a wide range of ecological indicators, indicators based on exergy (eco-exergy and specific eco-exergy) stand out for providing a universal language to compare different organisms and systems, based on concepts of physics. Although well-established as ecological indicators in temperate regions, little information exists on the use of eco-exergy and specific eco-exergy in tropical ecosystems. The objective of this thesis was to test the ability of ecological indicators based on exergy to evaluate the environmental conditions of different ecosystems in hydropower basins in neotropical savannah (Cerrado biome). For this purpose, this thesis is divided into three chapters where the aims were to characterize (1) the ecological effects of the presence of invading bivalves on the structure of benthic macroinvertebrate communities in neotropical reservoirs; (2) the influence of riparian forest canopy cover on the structure and functioning of benthic macroinvertebrate communities in reference condition headwater streams; (3) the influence of a small hydropower dam on the structure of benthic macroinvertebrate communities in the main channel of a high-order river. In the first chapter it was observed that the presence of invasive bivalves significantly increases the complexity of communities of benthic macroinvertebrates in neotropical reservoirs, represented by significantly higher values of eco-exergy and specific eco-exergy. This suggests that the invasive bivalves are integrated to the native communities, providing greater integration of the benthic community with the water column production. However, it was also verified that the presence of the invaders decreases the richness and biomass of the native species while increasing the biomass of the invading gastropod Melanoides tubertulata, which suggests an Invasion Meltdown scenario. In the second chapter the results show that the riparian canopy cover has an ecological significant effect on the secondary production and complexity of the benthic communities, which implies a dependence of these communities on autochtonous production in neotropical streams under reference conditions. In the third chapter, the sampling sites directly affected by the small hydroelectric dam in the Pandeiros river have eco-exergy and specific eco-exergy significantly different from the areas under the river's non-regulated hydrological regime. In conjunction with the dominance of invasive species, these results show that the presence of the dam significantly affects the structure of the benthic macroinvertebrate communities. These results show that eco-exergy and specific eco-exergy are good indicators for a wide range of neotropical aquatic environments capable of responding to various types of natural or atrophic alterations.